Chapter 3: Evidence-Based Practice (Foundations in Clinical Pharmacy Practice, 2025)
AuthorMr. Srihari Krishna Indurti, PharmD Intern, Department of Pharmacy Practice, East Point College of Pharmacy, Benguluru, Karnataka, IndiaAbstractEvidence-based pharmacy practice integrates best research evidence with clinical expertise and patient values to optimize medication therapy decisions. Literature evaluation skills include searching biomedical databases efficiently, understanding study designs, and interpreting statistical analyses to assess clinical significance beyond statistical significance. Clinical guideline interpretation requires evaluating recommendation strength, evidence quality, and applicability to specific patient populations while recognizing limitations and conflicts. Critical appraisal employs structured frameworks to evaluate literature validity, importance, and applicability through systematic assessment of methodology, bias risk, and result interpretation. Practical application involves integrating evidence with patient-specific factors including preferences, comorbidities, and social determinants through shared decision-making. This approach enables pharmacists to navigate information overload, resolve conflicting recommendations, address evidence gaps, and translate complex research into practical therapeutic decisions that balance scientific evidence with individualized patient care, ultimately improving medication therapy outcomes through rigorous, systematic application of best available evidenceKeywords: Clinical Literature Evaluation, Critical Appraisal, Guideline Implementation, Evidence Hierarchy, Therapeutic Decision-MakingVIEW PDF